Murder in an Irish pub [large type] - O'Connor, Carlene (O'Connor, Carlene. Irish village mystery., 2019)
In the small village of Kilbane in County Cork, for a cuppa tea or a slice of brown bread, you go to Naomi's Bistro, managed by the many siblings of the lively O'Sullivan brood. For a pint or a game of darts--or for the poker tournament that's just come to town--it's the pub you want. One player's reputation precedes him--Eamon Foley, a tinker out of Dublin, called the Octopus for playing like he has eight hands under the table. But when Foley is found at the end of a rope, swinging from the rafters of Rory Mack's pub, it's time for the garda to take matters into their own hands. Macdara Flannery would lay odds it's a simple suicide--after all, there's a note and the room was locked. But Siobhan suspects foul play, as does Foley's very pregnant widow. Perhaps one of Foley's fellow finalists just raised the stakes to life and death. With conflicting theories on the crime--not to mention the possibility of a proposal--tensions are running high between Siobhan and Macdara. Soon it's up to Siobhan to call a killer's bluff, but if she doesn't play her cards right, she may be the next one taken out of the game...